2016
DOI: 10.1007/s13105-016-0542-0
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dimorphism in obesity-related genes in the epicardial fat during aging

Abstract: Aging increases the risk of cardiovascular disease and metabolic syndrome. Alterations in epicardial fat play an important pathophysiological role in coronary artery disease and hypertension. We investigated the impact of normal aging on obesity-related genes in epicardial fat. Sex-specific changes in obesity-related genes with aging in epicardial fat (EF) were determined in young (6 months) and old (30/36 months) female and male, Fischer 344 × Brown Norway hybrid (FBN) rats, using a rat obesity RT2 PCR Array.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 47 publications
0
12
1
Order By: Relevance
“…Concerning sex-related differences in ectopic fat depots, the higher EFth observed in men may be ascribed to the well-known association existing between VAT extent and ectopic fat deposition. Sexual dimorphism in epicardial fat occurs in aging rats and this may be ascribed to differences in adipocytokines and obesity-related genes [14,15]. Also in human beings, the SWAN Cardiovascular Fat Ancillary Study reported increased EFth and coronary artery calcification in post-menopausal women, in association with decreased estradiol levels [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…Concerning sex-related differences in ectopic fat depots, the higher EFth observed in men may be ascribed to the well-known association existing between VAT extent and ectopic fat deposition. Sexual dimorphism in epicardial fat occurs in aging rats and this may be ascribed to differences in adipocytokines and obesity-related genes [14,15]. Also in human beings, the SWAN Cardiovascular Fat Ancillary Study reported increased EFth and coronary artery calcification in post-menopausal women, in association with decreased estradiol levels [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…By comparison, aged male rats showed an increased expression of genes for inflammatory cytokine, IL-6, in EAT [ 40 ]. Changes in obesity related genes in EAT were observed only in female rats, but not in males during aging [ 41 ]. This indicates that a dysfunctional EAT associated with aging demonstrates different metabolic and inflammatory activities between the two sexes.…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for the difference are unclear, but a possible cause is the difference of sexual dimorphism in EAT during aging. Experimental data revealed that EAT function decreased with aging in female rats but was relatively unchanged with age in male rats [26, 27]. These differences might help us to understand the sex differences of the relationship of EAT and CAS and change of these associations after menopause in women.…”
Section: Discussionmentioning
confidence: 99%